Box Pruning. Mecanización de la poda - Acosta, Gabriela Lourdes (2019)
Fil: Acosta, Gabriela Lourdes. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Mendoza; Argentina